2016
DOI: 10.1038/nbt.3702
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human embryonic stem cells to HOXA+ hemogenic vasculature that resembles the aorta-gonad-mesonephros

Abstract: The ability to generate hematopoietic stem cells from human pluripotent cells would enable many biomedical applications. We find that hematopoietic CD34 cells in spin embryoid bodies derived from human embryonic stem cells (hESCs) lack HOXA expression compared with repopulation-competent human cord blood CD34 cells, indicating incorrect mesoderm patterning. Using reporter hESC lines to track the endothelial (SOX17) to hematopoietic (RUNX1C) transition that occurs in development, we show that simultaneous modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
244
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(264 citation statements)
references
References 81 publications
19
244
0
1
Order By: Relevance
“…Following an initial period of BMP4-based mesoderm induction, brief inhibition of activin (Kennedy et al, 2012), or provision of a WNT agonist (Gertow et al, 2013) were sufficient to inhibit the erythroid-biased primitive programme. Importantly, activin inhibition (Kennedy et al, 2012), WNT stimulation (Sturgeon et al, 2014) or a combination of the two (Ng et al, 2016) from days 2-4 of in vitro differentiation also resulted in a bias towards definitive haematopoietic lineages, as defined by the capacity to generate T lymphocytes (Kennedy et al, 2012;Sturgeon et al, 2014).…”
Section: Mesoderm Induction and Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Following an initial period of BMP4-based mesoderm induction, brief inhibition of activin (Kennedy et al, 2012), or provision of a WNT agonist (Gertow et al, 2013) were sufficient to inhibit the erythroid-biased primitive programme. Importantly, activin inhibition (Kennedy et al, 2012), WNT stimulation (Sturgeon et al, 2014) or a combination of the two (Ng et al, 2016) from days 2-4 of in vitro differentiation also resulted in a bias towards definitive haematopoietic lineages, as defined by the capacity to generate T lymphocytes (Kennedy et al, 2012;Sturgeon et al, 2014).…”
Section: Mesoderm Induction and Patterningmentioning
confidence: 99%
“…The selective expression of HOXA genes in human foetal liver and UCB-derived haematopoietic progenitor and stem cells clearly distinguished them from PSC-derived haematopoietic progenitors generated using conventional mesoderm induction protocols (Dou et al, 2016;Ng et al, 2016). HOX genes mark axial position during development and are first expressed at the primitive streak stage (Deschamps and van Nes, 2005).…”
Section: Mesoderm Induction and Patterningmentioning
confidence: 99%
“…1 C and D). We also tested the function of BMP4 as it is widely used for AEC differentiation (6,9,12,13). The result showed that BMP4 suppressed the arterial marker (EFNB2) expression ( Fig.…”
Section: Cd144mentioning
confidence: 99%
“…S3 A and B). EFNB2 and EPHB4 were the first identified and most widely used markers for AECs and VECs, respectively (6)(7)(8)(9)(10)(11)(12)(13)17). Specific targeting of the EFNB2 and EPHB4 locus was confirmed by junction PCR and Southern blot analysis (SI Appendix, Evaluation of Candidate Factors for Arteriovenous Specification.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation